Pengaruh Pemahaman Akuntansi, Sistem Pengendalian Internal, dan Penerapan SAK EMKM Terhadap Kualitas Laporan Keuangan UMKM di Kota Batam - Karyaman Nazara; Argo Putra Prima (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the effect of accounting understanding, internal control systems, and the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the quality of MSMEs’ financial statements in Batam City. This research employs a quantitative approach using a cross-sectional survey design. Data were collected through questionnaires distributed to MSME owners and analyzed using multiple linear regression analysis. The results indicate that accounting understanding, internal control systems, and the implementation of SAK EMKM each have a significant partial effect on the quality of financial statements. Simultaneously, the three independent variables have a very strong influence on financial statement quality, with a coefficient of determination of 91.6%. These findings suggest that the integration of accounting competence, effective internal control, and compliance with accounting standards is essential to improve the reliability and accountability of MSMEs’ financial reporting. This study provides important implications for policymakers and stakeholders in designing training and assistance programs to strengthen financial management practices among MSMEs.